Assessing the dynamics of urban vulnerability to climate change: Case of Helsinki, Finland - Jurgilevich, Alexandra; Räsänen, Aleksi; Juhola, Sirkku (Elsevier Science, 2021)
Future climate risk is not only dependent on future climatic changes but also on how exposure and vulnerability develop in the future. There is a gap in understanding what drives future climate vulnerability, and how to account for its spatial emergence. This issue is particularly pertinent for cities due to the concentration of assets and population at risk, and rapid socio-economic and land use changes. We develop a mixed methods approach, which integrates quantitative, qualitative and participatory methods to (1) identify internal and external drivers of socio-economic development and land use change, (2) explore a range of future pathways using local socio-economic scenarios, and (3) visualize changes in vulnerability indicators with the help of a participatory mapping exercise. We test the approach in the City of Helsinki with the timeframe up to 2050. Our results show the connections between the drivers and changes in vulnerability indicators, while maps developed in a stakeholder workshop visualize the potential spatial changes in indicators. Our approach of connecting indicators, drivers and adaptation/planning needs, as well as scenario analysis, provides a deeper understanding of vulnerability dynamics as a process and provides insights for different sectors of urban policy and planning.
Keywords: Future vulnerability; Climate risk; Urban planning; Public participation GIS; Mixed methods; Socio-economic